The Ontological Status of Christian Eschatology (Journal of Research for Christianity in China (JRCC), 2023)
Chapter V , The Question of an Eschatological Ontology, in The Logic of Promise in Moltmann’s Theology, Christopher Morse, Philadelphia Fortress Press, 1979.